Mechanism of melanoma suppression by Prosopis juliflora derived alkaloids: Apoptosis induction and signaling pathway inhibition - Jasoda Choudhari; Snehal K. Nimal; Shridhar Chougule; Trupti Shinde; N.R. Dhatrak; Gopal C. Kundu; Rajesh N. Gacche (Phytomedicine Plus)
Background: Traditional medicines remain integral to healthcare worldwide especially in developing countries. Our prior studies highlighted the anti-melanoma potential of Prosopis juliflora leave methanolic extract (PJLME), leading us to further isolate and characterize bioactive compounds from PJLME and evaluate their efficacy against melanoma. In this context, we identified alkaloid fractions derived from PJLME (PJLME-AF) as key agents in PJLME's cytotoxic effect against melanoma cells. Purpose: The purpose of this research was to evaluate the anti-cancer effects and mechanisms of PJLME-AF on melanoma cell lines. Methods: Chemical Profiling of PJLME-AF was conducted by using LC-ESI-MS/MS. Cell viability and anti-migratory effects of PJLME-AF were assessed through MTT, wound healing and transwell assays. Mechanistic study of PJLME-AF was explored using ROS generation assay, apoptosis assays (Annexin V) assay, western blot (apoptotic protein, EMT markers, stem cell markers and signalling pathways), qPCR. In-vitro spheroid assay was performed to explored the PJLME-AF cytotoxic effects on tumour spheroid forming ability of melanoma cells. Additionally, the anti-tumor efficacy of PJLME-AF was tested in an in-vivo C57BL/6 mouse model. Results: PJLME-AF demonstrated potent anti-proliferative, anti-migratory and anti-invasive effects on melanoma cells. Mechanistic study indicates that PJLME-AF strongly induce ROS generation and subsequent apoptotic cell death in melanoma cells. Furthermore, PJLME-AF downregulated epithelial-to-mesenchymal transition (EMT) proteins, stem cell markers and Akt/Erk cell survival proteins providing insights into its molecular mechanisms. Notably, PJLME-AF inhibited spheroid formation and reduced PD-L1 expression. Finally, anti-tumor activity of PJLME-AF was further confirmed in a in-vivo mice model. Additionally, PJLME-AF combined with dacarbazine, exhibited enhanced cytotoxicity on melanoma compared to the drug alone. Conclusion: PJLME-AF exhibit promising natural anti-cancer agents for metastatic melanoma treatment. This research contributes to the development of novel, safe, and cost-effective agents for metastatic melanoma treatment and as a potential candidate for further cancer research.